750 TWT-101: a first-in-clinic, phase 1/2 study of CFI-402411, a hematopoietic progenitor kinase-1 (HPK1) inhibitor, as a single agent and in combination with pembrolizumab in subjects with advanced solid malignancies - Papadopoulos, Kyriakos; Fu, Siqing; Hamilton, Erika; Spira, Alexander; Scott, Laurie; Wang, Judy; Ma, Brigette; Spreafico, Anna; Sharma, Manish; Chu, Quincy; Bray, Mark; Michelson, Glenn; et al. (Journal for immunotherapy of cancer, 2022)
BackgroundCFI-402411 is a potent inhibitor of HPK1 (Hematopoietic progenitor kinase 1), a protein serine/threonine kinase that negatively-regulates T-cell activation. Following T-cell receptor engagement, HPK1 phosphorylates SLP-76, to down-regulate signals required for T-cell activation and proliferation1,2. CFI-402411 is expected to relieve HPK1-mediated inhibition of T-cell activation, facilitating an anti-tumor immune response.MethodsIn this ongoing phase 1 study, part A evaluates CFI-402411 daily dose in dose escalation cohort (3+3 design) and dose expansion, part B evaluates CFI-402411 in combination with pembrolizumab in dose escalation (BOIN design) and dose expansion in pembrolizumab eligible tumors. Dose limiting toxicity (DLT) is any grade ≥3 toxicity in the first cycle of therapy (21d cycles). Starting dose was 80mg.ResultsAs of 14 May 2022 (data cutoff), 25 and 9 patients (pts) enrolled to A and B respectively. Median age was 62 (30-79). Median cycles of treatment were 3 (range: 0-20). Majority of patients were male (A, 60% and B, 78%). Median prior regimens were 2 (range: A, 1-4; B, 1-3). 6pts (A, 24%) and 5pts (B, 56%) received prior anti-PD-1/anti-PD-L1 inhibitor. Diagnoses in ≥2pts for A: colorectal (6pts), pancreatic (5pts); for B: small cell lung cancer (2pts). 8 dose levels (80 to 800 mg) have been studied in A, 2 dose levels (60 and 80 mg) in B. TEAEs occurring in ≥40% of A pts: diarrhea (n=17, 68%), nausea (n=11, 44%), decreased appetite (n=10, 40%); and B: vomiting (n=4, 44%). 19pts (76%) in A and 6pts (67%) in B experienced CFI-402411 related AEs. Immune-related AEs were reported in 1pt (A; 4% [ALT and AST increase]) and 2pts (B; 22% [febrile illness, flu-like symptoms]). Grade ≥3 AEs and serious AEs occurred in 14pts (56%) and 10pts (40%) in A; and 3pts (33%) and 4pts (44%) in B. DLTs occurred in 2pts (A [800mg]: diarrhea, spinal cord compression) and 1pt (B [80mg+pembro]: flu-like symptoms). No novel toxicity signals were seen. Disease control rates were 24% in A (6/25) and 44% in B (4/9). One B patient (11%), squamous head and neck cancer (H&N) previously treated with pembrolizumab, has confirmed partial response (PR) and remains on treatment, 8 cycles. An additional H&N patient treated with monotherapy CFI-402411 achieved unconfirmed PR after data cut.ConclusionsCFI-402411 is a well-tolerated, potent inhibitor of HPK1 with a manageable AE profile and initial evidence of activity. RP2D and additional safety and efficacy data will be reported at conference presentation.AcknowledgementsTreadwell Therapeutics would like to thank both the patients and the research staff at enrolling centers who have helped to bring this novel therapy to the clinic.Trial RegistrationNCT04521413ReferencesHu MQ. Human HPK1, a novel human hematopoietic progenitor kinase that actives the JNK/SAPK kinase cascade. Genes & Development. 1996;10:2251–2264.Lasserre RC-G. Release of serine/threonine-phosphorylated adaptors from signaling microclusters down-regulates T cell activation. Immuno Res. 2011;295:839–853.Ethics ApprovalThis study obtained ethics approvals at the following ethics/IRB’s;Papadopoulos, KP; Advarra IRB ID: Pro00051609Fu, S; University of Texas MD Anderson Cancer Center Office of Human Subject Protection IRB ID 2020-0678Hamilton, E; Advarra IRB ID: Pro00051611Spira, A; Advarra IRB ID: Pro00043629Laurie, S; Ontario Cancer Research Ethics Board, CTO Project ID 3320Wang, J; Advarra IRB ID: Pro00051611Ma, B; Joint Chinese University of Hong Kong-New Territories East Cluster Clinical Research Ethics Committee CREC Ref. No .: 2020.367-TSpreafico, A; Ontario Cancer Research Ethics Board, CTO Project ID 3320Sharma, M; Advarra IRB: ID Pro00051609Chu, Q; Health Research Ethics Board of Alberta Ethics ID: HREBA.CC-20-0504_REN1Hamid, O; WCG, IRB: IRB Tracking Number: 2020236As evidenced by verified clinical database information all subjects gave informed consent before taking part in this clinical trial.